A study on the effect of local student satisfaction, institutional image and student commitment towards student loyalty in private universities of Malaysia - Au, Poh Yee; Chan, Pui Yee; Loke, Pui Hoong; Tan, Ti Seng (2017)
The purpose of this study is to investigate the effect of local student satisfaction, institutional image and student commitment towards student loyalty in private universities in Malaysia. A total number of 250 questionnaires were distributed to local university students in private sector. Those respondents are selected using convenience sampling technique, at five university and university college campuses in Malaysia. Of this, 200 were deemed fit for analysis (81.60 per cent response rate). Statistical Package for the Social Sciences (SPSS) was adopted to analyze the collected data, assess the model and test hypotheses. The findings indicate that all three independent variables have positively and significantly influence student loyalty. Nevertheless, there are a number of limitations associated with this study. First, the findings of the study are based on data from local students at only five Malaysian private university and university college campuses. Next, this study focuses on a relatively small sample of local private students. Besides, there is limited source of journals and articles database for researchers to access. Apart from this, the study validates the HEdPERF scale in the context of Malaysian private universities with regard to the perceptions of local students which might exclude some factors that may influence their level of satisfaction. On the other hand, this study highlights a number of implications for the management of Malaysian private universities. It delivers a valuable insight for government or universities especially those in private sector to enhance the service quality of higher education institutions. The findings are able to provide greater attention on the quality of education being offered by educational institutions worldwide, all in the pursuit of academic excellence.